Correction of Maxwell equations - Лёзов, П.П. (Radiotekhnika, 2012)
Hypothesis of Maxwell equations in the form of the first integral equation named for him is considered and it is shown that this hypothesis has no basis. Electric current of the single-path conductor creates the ring or circular electric field in the dielectric surrounding atmosphere, far in its form from the vortex field. Circulation of the electric intensity vector itself cannot cause anything in the environment as it is a consequence of the electric current passage in a closed conductor.